Fazer justiça à história: memórias e identidades no Centro de Memória e Cultura do Poder Judiciário do Estado de Goiás - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
This research analyzes how the Goiás’ Judiciary Power intends to reintegrate Justice into social memory in a way to foment the feeling of belonging and of identification between the state and the society in which it is inserted through its Cultural and Memory Center. The objective is to contribute to the expansion of knowledge production in the field of Memory and, more specifically, Memory in jurisdictional bodies, as well as subsidizing the complex work carried out by the teams that work in these places. For a better understanding of the object, we combined documentary and bibliographic research with a qualitative approach. The analyzes allowed us to understand that the goods, including the TJGO's CMC operating space itself as well as what constitutes and may make up its collection, transcend the tangible nature of the institution, given the cultural and historical value they have, and which is not restricted to the body to which they are linked. Therefore, we propose the elaboration of a catalog so that the collections of the Judiciary Power's Memory and Culture Center of Goiás State-GO can be known, studied and reinterpreted, enabling the construction of new memories for the most diverse social groups, transcending the institutional memory consolidated.
Doing justice to the history: memories and identities in the Center of Memory and Culture of the Judiciary of Goiás State
Keywords: Memória; Centro de memória; Poder Judiciário, TJGO; Memory; Memory center; Judiciary Branch, TJGO; CIENCIAS HUMANAS::HISTORIA